ANALISIS KEBUTUHAN MEDIA FLASHCARD PADA PEMBELAJARAN IPAS MATERI RANTAI MAKANAN UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA SISWA KELAS V SEKOLAH DASAR - Naufal Abdurazak; Suriswo; Rahmad Agung N (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to develop a learning media in the form of flashcards for the IPAS (Ilmu Pengetahuan Alam dan Sosial) subject, specifically focusing on the topic of food chains, with the goal of improving the learning achievement of fifth-grade students in Pangkah Subdistrict, Tegal Regency. Initial observations conducted in the classroom revealed that many students struggled to understand the concept of food chains. This difficulty was evident from their low academic performance, with many students scoring below the KKTP (Minimum Mastery Criteria) standard. To address this issue, the research utilizes the ADDIE development model, which includes five stages: Analysis, Design, Development, Implementation, and Evaluation. The needs analysis, carried out through interviews and observations with teachers and students, showed strong enthusiasm and a high demand for interactive and visually engaging learning tools. The findings suggest that the development of flashcards is both relevant and necessary to improve students’ conceptual understanding. In addition, flashcards serve as a motivational tool that can increase students’ focus, engagement, and active participation during IPAS learning activities, ultimately leading to better academic outcomes.